2010
DOI: 10.1111/j.1479-828x.2009.01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal outcomes in the Torres Strait Islands with a sixfold increase in type 2 diabetes in pregnancy over six years

Abstract: A massive increase in DIP was seen. The neonatal outcomes improved slightly. There is need for improvement in follow-up of gestational diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 24 publications
0
34
1
Order By: Relevance
“…The full text was unobtainable for 3 studies (68)(69)(70). Of the remaining 100 studies, 47 were excluded for the following reasons: multiple reports of the same study population (32,(71)(72)(73)(74), selective study population (including studies in which all women intended to breastfeed) (32,40,58,64,(75)(76)(77)(78)(79), only qualitative data reported (43,80,81), or no suitable data on breastfeeding reported . The remaining 53 studies were included in the systematic review ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full text was unobtainable for 3 studies (68)(69)(70). Of the remaining 100 studies, 47 were excluded for the following reasons: multiple reports of the same study population (32,(71)(72)(73)(74), selective study population (including studies in which all women intended to breastfeed) (32,40,58,64,(75)(76)(77)(78)(79), only qualitative data reported (43,80,81), or no suitable data on breastfeeding reported . The remaining 53 studies were included in the systematic review ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies (12,40,45,56,124,133) included only primiparous women. A random-effects meta-regression showed that the OR for early breastfeeding in these studies was not significantly different from the OR for studies that included all women (OR: 1.14; 95% CI: 0.65, 1.99; P = 0.64).…”
Section: Paritymentioning
confidence: 99%
“…3 Cape York in Far North Queensland had a population of 11 699 in the 2006 census, 51.3% identified as Indigenous. 5 This compares with the prevalence of DIP in the general Queensland population of 5.0% in 2005. 4 The prevalence of DIP amongst Cape York's geographical neighbour, the Torres Strait Islands, was recorded at approximately 13% in 2006, with 4.6% having T2DM and 8.7% GDM.…”
Section: Introductionmentioning
confidence: 84%
“…However, female patients seem to be at increased risk of gestational diabetes mellitus which is a well-known predictor of future type 2 diabetes. [2231]…”
Section: Discussionmentioning
confidence: 99%